Political incentives and state subsidy allocation: Evidence from Hungarian municipalities - Balázs Muraközy; Álmos Telegdy (Hungarian Academy of Sciences, Institute of Economics, 2015)
Using application-level data on successful and rejected applications for the European Union's Structural and Cohesion Funds between 2004 and 2012 in Hungary, we study which grant types are susceptible to political manipulation and how politicians achieve this goal. Using township fixed-effect estimators to attenuate the simultaneity bias between municipality characteristics and political affiliation, we find that townships with a mayor endorsed by the governing parties obtain 10 percent higher grant value per capita. This effect varies widely by grant attributes: it is of 16-19 percent when the applicant is a public entity or the project's purpose is construction so it is visible to voters and thus may bring about electoral benefits. For private applications and non-construction grants, where electoral gains are likely to be limited, the estimated effect is zero. Decomposing the township alignment effect into grant application effects (application intensity and the average value of grant) and grant decision effects (grant success rate and proportion of grant value received) reveals that both margins play a role in the political manipulation of grant distribution. When analyzing the effect of grants on votes, we show that voters indeed reward construction and public projects.
Keywords: D72; D78; H77; 330; Redistributive politics; Political alignment; European Structural Funds; Hungary